Optimization Allocation of Resources for Massive Manufacturing Service Requests - ZHANG Hong-guo; SHI Yan-lei; MA Chao; ZHANG Shu-li; LIU Sheng-hui (Journal of Harbin University of Science and Technology)
Aiming at how to efficiently handle the massive temporal sequential manufacturing service request in cloud manufacturing service platform, this paper proposes a service response timeoriented service request segmentation algorithm. The manufacturing task similarity distance algorithm is used to guarantee the segmentation algorithm accuracy. Then the correlated region is constructed under the premise of ensuring the integrity of manufacturing service request. On the basis of this, a manufacturing service resources allocation algorithm based on correlated region is proposed so as to ensure the equal distribution of manufacturing service resources in temporal dimensions, and then to improve the efficiency of the global optimization of the manufacturing service resources in the case of limited resources. Finally, the correctness and validity of the algorithm are proved by experiment and analysis.